Acid-Catalyzed Conversion of Cellulose Into Levulinic Acid With Biphasic Solvent System - Ma, Changyue; Cai, Bo; Zhang, Le; Feng, Junfeng; Pan, Hui (Frontiers in Plant Science, 2021)
In this work, directional conversion of cellulose into levulinic acid in a biphasic solvent system was developed. Compared to a series of catalysts investigated in this study such as metal salts (e.g., Al2(SO4)3, Fe2(SO4)3, Cr2(SO4)3, AlCl3, FeCl3 and CrCl3), and other solid acid catalysts like zeolite (HZSM-5) and resin (Amberlyst-15), the Amberlyst-15 as a more efficient acid catalyst was used in the hydrolysis of cellulose and further dehydration of derived intermediates into levulinic acid. Besides, biphasic solvent system can promote the conversion of cellulose and suppress the polymerization of the by-products such as lactic acid. The reaction conditions, such as temperature, time and catalyst loading were changed to investigate the effect on the yield of levulinic acid. The results indicated that an appealing LA yield of 82.72 mol% was achieved at 200 ℃ and 180 min with Amberlyst-15 catalyst in GVL/H2O under 4 MPa N2 pressure. The influence of different amounts of NaCl addition to this reaction was also investigated. This study provides an economical and environmental-friendly method for the directional conversion of cellulose and high yield of value-added chemical.